Dynamics of the interaction between the receptor-binding domain of SARS-CoV-2 Omicron (B.1.1.529) variant and human angiotensin-converting enzyme 2 - Priya Antony; Amie Jobe; Ranjit Vijayan (PeerJ, 2022)
Background The COVID-19 pandemic is still a global public health issue. Omicron, a SARS-CoV-2 B.1.1.529 variant, has raised concerns about transmission and vaccine effectiveness. Omicron currently has the greatest number of variantions. Methods To gain a better understanding of the significance of these variations and the dynamics of the interaction between the Omicron spike (S) protein and its human host factor angiotensin-converting enzyme 2 (ACE2), triplicate 500 ns molecular dynamics simulations were run using the structure of the S protein’s receptor-binding domain (RBD) in complex with ACE2. The interaction and binding energy, determined using the molecular mechanics—generalized Born surface area approach, were compared to the original SARS-CoV-2 and the B.1.617 variant. Results Though mutations K417N and G496S in the S protein RBD disrupt interactions found in the original SARS-CoV-2 complex, mutations Q493R and N501Y introduce interactions not found in the original complex. Interaction at a key viral hotspot and hydrophobic contacts at ACE2’s N-terminus were preserved, but intermolecular hydrogen bonds and polar contacts in the S-ACE2 interface were lower than in the original SARS-CoV-2 interface.